Biology-driven approaches to prevent and treat relapse of myeloid neoplasia after allogeneic hematopoietic stem cell transplantation - Zeiser, Robert; Beelen, Dietrich W.; Bethge, Wolfgang Andreas; Bornhäuser, Martin; Bug, Gesine; Burchert, Andreas; Christopeit, Maximilian Erich Joachim; Duyster, Justus; Finke, Jürgen; Gerbitz, Armin; Klusmann, Jan-Henning; Kobbe, Guido; et al. (Biology of blood and marrow transplantation, 2019)
Relapse, acute myelogenous leukemia, myelodysplastic syndrome, allogeneic hematopoietic stem cell transplantation